The Optimum Concentration of Lime Juice as Acidifier on Mozzarella Cheese Manufacturing - Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2008)
The objectives of current research were to study the potency of lime juice as acidifier on Mozarella cheese physical quality. The method used in this research was completely randomized design. The experiment of variation of lime juice was repeated 4 times including 6 treatments were : L1=1.5%, L2=1.6%, L3=1.7%, L4=1.8%, L5=1.9% and L6=2.0% (v/v). The variablesÂ were rendement, meltability, strechability, and elasticity. Variation analysis on rendement, stretchability, and elasticity of Mozarella cheese showed that the use of those lime juice concentration gave no significant difference (P>0.05). However, those treatments gave significant different (P<0.05) on meltability of Mozarella cheese. The range of cheese rendement was about 11.00-11,93%. The highest meltability was on 1.9% concentration of lime juice. Therefore, it could be concluded that 1.9% concentration of lime juice was better for making Mozarella cheese as the highest value on rendement, meltability, strechability than the other concentration. Â Keywords: lime juice, Mozarella cheese